Age-Dependent Association Between Elevated Homocysteine and Cognitive Impairment in a Post-stroke Population: A Prospective Study - Zhou, Shengnan; Chen, Jiahao; Cheng, Lin; Fan, Kaili; Xu, Minjie; Ren, Wenwei; Chen, Yunbin; Geng, Dandan; Cheng, Haoran; Luan, Xiaoqian; Song, Jiaying; Lin, Gangqiang; et al. (Frontiers in Nutrition, 2021)
Background and Purpose: The results regarding the independent association between homocysteine (Hcy) levels and post-stroke cognitive impairment (PSCI) were inconsistent. The effect of age on this association has yet to be explored. The aim of this study is to determine the relationship between Hcy levels, age and cognitive impairment in a post-stroke population. Methods: A total of 592 patients with acute ischemic stroke completed follow-up. Serum Hcy levels were measured enzymatically by spectrophotometry within 24 h of admission. Cognitive function was evaluated by the Mini-Mental State Examination (MMSE) 1 month after stroke, and the scores ≤24 were considered as cognitive impairment. Our study was dichotomized into two group by a cut-off of 65 y. Multivariate logistic regression models were used to determine the association between baseline Hcy levels and cognitive impairment. Results: According to the MMSE score, 317(53.5%) patients had cognitive impairment. Patients with higher levels of Hcy were more prone to have cognitive impairment 1 month after stroke than patients with lower levels of Hcy (p < 0.001). The optimal cut-off points of Hcy level (μmol/L) were (T1) ≤ 8, (T2) 8–12, and (T3) ≥ 12. After adjusting for confounding factors, the multivariate regression analysis showed the third Hcy tertile was independently associated with cognitive impairment (OR = 2.057, 95% CI =1.133–3.735, p = 0.018). A stronger association [T2 (OR = 2.266, 95%CI = 1.042–4.926, p = 0.039); T3 (odds ratio =3.583, 95%CI = 1.456–8.818, p = 0.005)] was found in the younger group. However, the independent association was not confirmed in the older group. Conclusions: Elevated Hcy levels in the acute phase of ischemic stroke were independently associated with cognitive impairment in a post-stroke population. Furthermore, the association was age-dependent and more meaningful in a younger population aged below 65. So, Hcy levels in patients with stroke should be well monitored, especially in younger patients.